PERSEPSI PETANI MENABUNG DI BANK RAKYAT INDONESIA UNIT SONDER - Mario Arron Sumolang; Grace Adonia Josefina Rumagit; Lyndon Reinhard Jacob Pangemanan (Sam Ratulangi University, 2019)
The purpose of this study was to determine the perceptions of farmers saving at Bank Rakyat Indonesia Sonder Unit. This research has been carried out for three months, namely from April 2019 to June of 2019 starting from preparation to preparation of research reports. The sampling method in this study was intentional (purposive sampling) The data used in this study were primary and secondary data. Primary data is data obtained directly from 79 farmers who save at Bank Rakyat Indonesia Unit Sonder using a questionnaire. Secondary data is data obtained from PT. Bank Rakyat Indonesia Unit Sonder, such as data on consumer saving farmers. The analytical method used in this study is descriptive analysis method and uses Likert scale analysis. The results of this study indicate that the perception of farmers saving at Bank Rakyat Indonesia Unit Sonder belongs to the Satisfied category. .+eprm*